Mercury contamination in the Madeira River, Amazon. Hg inputs to the environment - Lacerda, Luiz Drude de (1989)
The potential contamination of Amazon rivers by Hg used in gold-mining activity has recently worried various l and international environmental authorities. Because of the great quantities of Hg involved, the complex ecology Amazonian ecosystems and the socio-economy of the local population, generally based on fishery resources, are at r Some attempts have been made to quantify the problem (Mallas & Benedicto 1986), however logistic difficultie and lack of reliable information have led to some misinformation. In 1986 three Brazilian research groups at Universities of Rondonia, Niteroi, and Rio de Janeiro started a joint project on the Madeira River to quantify contamination in the area. This note presents the first estimates of Hg inputs to the regional environment, descri the evolution of the problem, and discusses its eventual impact on the local biota and human population. The Madeira River is located in the southwestern Amazon basin and drains a watershed covered mostly by tropi rain forests, although in recent years accelerated deforestation has occurred in localized areas under the "Polo Noroe project (Fearnside 1986). Most gold-mining occurs in the Madeira River itself along 300 km from Porto Velho capital of the State of Rondonia, along the Bolivian border, to the town of Guaraja Mirim (Fig. 1). The "gold rush" in the Madeira River started in 1975 as a nonmechanical activity, mostly on the river margin and sand banks during the dry season. This was rapidly followed by the use of boats and divers, then by mechan dredges, to the extent that in 1985, 1500 pieces of equipment were working the river, 800 of them mechan dredges (DNPM 1983, pers. comm.). [...]